Design and Fabrication of Automatic Weight, Color and Height Based Sorting System - Arafath Al Fahim; Mohammad Mizanur Rahman; Homayun Kabir; Samiul bari (Asosiasi Staf Akademik Perguruan Tinggi Seluruh Indonesia (ASASI), 2023)
Sorting is a necessary task that is frequently performed in daily life. Manual sorting is an expensive, difficult, and drawn-out operation. Additionally, it slows down manufacturing operations. To solve these issues the sorting system now uses Low-Cost Automation which aims to decrease labor costs, manufacturing times, and processing complexity while also enhancing product quality, boosting output, etc. In this research, an efficient technique for automatically sorting the object based on color, height, and weight has been devised. The objects are recognized, separated, and collected using a collection bin along with a conveyor belt, strain gauge load cell, TCS34725 RGB color sensor, ultrasonic sensor, extra channel path, etc. according to their colors. The Arduino Uno controls the entire operation of this system. Here, three types of products are sorted based on their weight, color, and height. These three colors are red, blue, and green. Firstly, the weight is measured using strain gauge load cells. Then the color of the product has been detected by the color sensor at the same stage, and according to the color collecting bin rotates to the desired angle. Finally, the height is measured by an ultrasonic sensor. An extra channel is used at the end of the conveyor belt. At the end of the channel, a three-portion collecting bin is kept. The bin can be rotated at the desired angle by a servo motor after detecting the specified color object, and objects are being collected from this bin. Thus, the objects are sorted out based on their weight, color, and height. The experimental results show that the system fits the design requirements, is dependable, and has high sorting accuracy.